A Five-Level Common-Ground-T-Type Inverter for Solar Photovoltaic Applications - Lee, Sze Sing; Yang, Yongheng; Lee, Kyo Beum (IECON Proceedings (Industrial Electronics Conference), 2020)
In this paper, a novel 5-level inverter with common ac and dc ground is proposed for solar photovoltaic (PV) applications. The newly established common-ground-T-type (CGT-type) inverter is a single-stage topology restructured from the combination of a classical T-type inverter and a front-end three-level boost converter. Its distinctive topological structure can effectively eliminate the common mode voltage issue, prevent leakage currents, and ensure a continuous input current in PV systems. More importantly, it requires only two capacitors to realize an ac voltage which can be significantly boosted from a single dc source. A pulse width modulation (PWM) scheme is also established to undertake the following tasks simultaneously: charging of the boost inductor with a constant duty-cycle, and switching of two capacitors for 5-level ac voltage generation. The operation and feasibility of the proposed CGT-type inverter is analyzed and validated through simulation results.
Keywords: BOOST converter; Boost inductors; Common mode voltage; Continuous input; Single dc source; Single stage topology; Solar photovoltaics; Topological structure; 5-level; common-ground; solar PV; T-type inverter; voltage boosting